Micro-expansion self-compacting concrete and preparation method thereof
By using a composite expansion agent made from modified plant protein and modified alum stone, the shrinkage and fluidity problems of self-compacting concrete are solved, improving the expansion performance and self-compacting properties of concrete. It is suitable for construction of complex structures, especially in complex structures where it can automatically fill voids during construction, reduce bleeding and segregation, and improve construction efficiency.
Patent Information
- Application Number
- CN202511134125.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-11-18
AI Technical Summary
Self-compacting concrete is prone to shrinkage and creep after hardening, which can lead to cracking and reduced fluidity, affecting construction quality and efficiency.
A composite expansion agent consisting of modified plant protein and modified alum stone is used. The modified plant protein generates small molecule peptides and calcium ion complexes, and the modified alum stone is grafted with a polymer layer to form a three-dimensional network structure, thereby enhancing the expansion performance and fluidity of concrete.
It improves the early strength and later durability of concrete, reduces cracking, improves rheological properties, achieves self-compacting and anti-segregation properties, and is suitable for construction of complex structures.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of concrete, and particularly relates to a micro-expansion self-compacting concrete and a preparation method thereof. BACKGROUND
[0002] Self-compacting concrete is a new type of high-performance concrete made by using modern concrete technology on the basis of greatly improving the performance of ordinary concrete. The self-compacting concrete is poured into a steel pipe to form a steel pipe concrete, which has many advantages such as high bearing capacity, small quality, good plastic toughness, and convenient construction, and is widely used in super high-rise buildings, bridge arches and other structures. Compared with ordinary concrete, the self-compacting concrete can improve the construction speed and reduce the engineering cost by using the pouring method without vibration, and the construction periphery is free from noise pollution.
[0003] With the vigorous development of infrastructure in recent years, high-strength, self-compacting and expansive concrete is increasingly used in arch bridge steel pipes, and has produced certain economic benefits. However, the design of the mix proportion of self-compacting concrete has the characteristics of high sand ratio, low water-binder ratio and high mineral admixture content. The shrinkage and creep of self-compacting concrete with more paste and less coarse aggregate after hardening will be larger, which is easy to cause cracking of the concrete.
[0004] In order to solve the shrinkage problem of self-compacting concrete, it is an inevitable trend to add expansive agent to high-performance concrete. Therefore, it is of important practical significance to select appropriate raw materials, study the mix proportion and performance of self-compacting concrete, solve the problem of poor fluidity of self-compacting concrete admixture with expansive agent, and study the mechanical properties of expansive self-compacting concrete, which is of important practical significance for the promotion of expansive self-compacting concrete. SUMMARY
[0005] The purpose of the present application is to provide a micro-expansion self-compacting concrete which has good self-compacting, anti-segregation and excellent gap passing property, and excellent overall workability.
[0006] To achieve the above technical purpose, the technical scheme adopted by the present application is: A micro-expansion self-compacting concrete, comprising the following raw materials by weight: cement 400-460 parts, fly ash 50-120 parts, mineral powder 50-80 parts, natural sand 570-850 parts, gravel 800-1100 parts, composite expansive agent 10-15 parts, polycarboxylic acid water reducer 8-15 parts, water 150-160 parts, water retaining agent 4-6 parts.
[0007] Further, the composite expansive agent comprises modified plant protein and modified alunite, and the mass ratio of the two is 1:2.
[0008] Further, the preparation method of the modified plant protein is: (1) Protein extraction: The duckweed was washed with clean water, dried at 50°C until the moisture content was <10%, and then sieved through a 100-mesh screen. The plant protein was extracted by alkali dissolution and acid precipitation to obtain duckweed protein powder; (2) Enzymolysis: 10 g of duckweed protein was dissolved in 100 mL of PBS, 0.1 g of alkaline protease was added, the pH was adjusted to 9.0, and the mixture was hydrolyzed at 37°C for 4 h. The enzyme was inactivated by heating at 100°C for 10 min, and the hydrolyzed protein was collected by centrifugation; (3) Graft copolymerization: The hydrolyzed protein was dissolved in 100 mL of deionized water, the pH was adjusted to 9.0, 1 g of sodium methacrylsulfonate and 0.1 g of 5% ammonium persulfate were added, and the mixture was reacted at 50°C for 3 h. The pH was adjusted to 7.0, and the mixture was freeze-dried; (4) Cross-linking modification: The glutamine transpeptidase was dissolved in 10 mL of deionized water and stirred for 30 min. The grafted protein was dispersed in 100 mL of PBS, and the glutamine transpeptidase solution was slowly added dropwise. The pH was adjusted to 6.5, and the mixture was reacted at 50°C for 2 h. The pH was then adjusted to 7.0 to terminate the reaction. The mixture was centrifuged and freeze-dried to obtain the modified plant protein.
[0009] Further, the amount of glutamine transpeptidase used in step (4) is 3% of the mass of the grafted protein.
[0010] Further, the preparation method of the modified alunite is as follows: (1) The alunite was soaked in a 1% sulfuric acid solution at 60°C for 1 h to obtain activated alunite; (2) KH-560 was added to an ethanol solution, and then the activated alunite was added. The mixture was reacted at 70°C for 1 h under a nitrogen atmosphere, washed with ethanol, and dried; (3) Glycidyl methacrylate and initiators potassium persulfate and ascorbic acid were added to the alunite prepared in step (2) in an amount of 8-12% of the mass of the alunite. The mixture was reacted at 50°C for 3 h under a nitrogen atmosphere. The reaction product was washed with deionized water three times and dried to pass through a 200-mesh screen to obtain the modified alunite.
[0011] Further, the mass ratio of the activated alunite, KH-560, and the ethanol solution in step (2) is 100:5:300, and the mass ratio of ethanol and water in the ethanol solution is 95:5.
[0012] Further, the amount of potassium persulfate added in step (3) is 0.3% of the mass of the alunite prepared in step (2), and the amount of ascorbic acid added is 0.15% of the mass of the alunite prepared in step (2).
[0013] Further, the water-retaining agent includes cellulose ether and high-molecular-weight water-absorbing resin, and the mass ratio of the two is (1-3):1.
[0014] A preparation method of a micro-expansion self-compacting concrete, comprising the following steps of preparation: First, a composite expansion agent is prepared, and cement, fly ash, mineral powder, natural sand, gravel and other dry materials are added into a mixer and dry-mixed for 2-3 minutes until uniform; then the composite expansion agent and a polycarboxylate superplasticizer are mixed and slowly added into the dry materials, and stirred for 3-5 minutes; finally, water and a water retaining agent are added to form a uniform slurry, and the micro-expansion self-compacting concrete is obtained.
[0015] The modified plant protein is added, and first, the protein is hydrolyzed to generate small molecular polypeptides, and the polar groups are exposed to enhance the chelating ability with calcium ions; the sodium methallyl sulfonate is grafted with anionic groups on the protein chain, the product can adsorb calcium ions to form a complex, and local expansion is induced; the glutamine transaminase is used to crosslink the protein molecules to form a three-dimensional network structure, and the dissolution is delayed and the expansion rate is controlled.
[0016] The modified alunite is added, and the grafting reaction of the glycidyl methacrylate on the surface of the alunite can form a polymer layer with expansion capacity, which is helpful to compensate the shrinkage deformation of the concrete, improve the compactness and crack resistance of the concrete. Meanwhile, the micro-expansion effect can improve the early strength and late durability of the concrete, and reduce the generation of cracks. In addition, the surface modification of the modified alunite makes it have better dispersibility and fluidity, which is helpful to improve the rheological properties of the concrete, so that it can automatically fill the voids in the construction process, reduce the bleeding and segregation phenomenon, and thus improve the self-compacting property. The concrete of the application can obtain good compactness without vibration, and is suitable for the construction of complex structures.
[0017] Advantages (1) The modified protein is used for cement hydration reaction in the application, and a protein-calcium ion complex is generated to fill the pores by volume expansion, and the grafted sulfonic acid groups adsorb water to form an osmotic pressure to drive the expansion.
[0018] (2) In the application, the modified alunite is prepared by the three-step method of activation, surface modification and polymerization reaction, and the glycidyl methacrylate is successfully introduced into the surface of the alunite to form a modified material with micro-expansion and self-compacting properties.
[0019] (3) The modified plant protein and the modified alunite are compounded in the application, and the two components synergistically act to make the composite expansion agent have a significant positive effect in the concrete, especially in the aspects of fluidity, segregation resistance, gap passing property and self-compacting property. DETAILED DESCRIPTION
[0020] The technical solutions of the application are further described below in combination with specific embodiments, but are not limited thereto.
[0021] Example 1 A kind of micro-expansion self-compacting concrete, comprising the following raw materials by weight: cement 400 parts, fly ash 50 parts, mineral powder 50 parts, natural sand 570 parts, gravel 800 parts, composite expansion agent 10 parts, polycarboxylic acid water reducing agent 8 parts, water 150 parts, water retaining agent 4 parts.
[0022] The composite expansion agent comprises modified plant protein and modified alunite, and the mass ratio of the two is 1:2.
[0023] The preparation method of the modified plant protein is: (1) Protein extraction: Lemna is washed with clean water, dried at 50 DEG C until the moisture content is less than 10%, and then sieved through a 100-mesh screen. The plant protein is extracted by alkali dissolution and acid precipitation to obtain Lemna protein powder; (2) Enzymolysis: 10 g of Lemna protein is dissolved in 100 mL of PBS, 0.1 g of alkaline protease is added, the pH is adjusted to 9.0, and hydrolysis is carried out at 37 DEG C for 4 h. The enzyme is inactivated by heating at 100 DEG C for 10 min. The hydrolyzed protein is collected by centrifugation. (3) Graft copolymerization: the hydrolyzed protein is dissolved in 100 mL of deionized water, the pH is adjusted to 9.0, 1 g of sodium methacrylsulfonate and 0.1 g of 5% ammonium persulfate are added, and reaction is carried out at 50 DEG C for 3 h. The pH is adjusted to 7.0, and the product is freeze-dried. (4) Cross-linking modification: glutamine transaminase is taken and 10 mL of deionized water is added, and stirring is carried out for 30 min. The graft copolymerized protein is dispersed in 100 mL of PBS, and the glutamine transaminase solution is slowly added dropwise. The pH is adjusted to 6.5, and reaction is carried out at 50 DEG C for 2 h. The pH is adjusted to 7.0 to terminate the reaction. The product is centrifuged and freeze-dried to obtain the modified plant protein.
[0024] The amount of glutamine transaminase used in step (4) is 3% of the mass of the grafted protein.
[0025] The preparation method of the modified alunite is: (1) Alunite is soaked in a 1% sulfuric acid solution at 60 DEG C for 1 h to obtain activated alunite; (2) KH-560 is added to an ethanol solution, and then the activated alunite is added. Reaction is carried out at 70 DEG C for 1 h under a nitrogen atmosphere, and then the product is washed with ethanol and dried; (3) 8% glycidyl methacrylate, initiator potassium persulfate and ascorbic acid are added to the alunite prepared in step (2), and reaction is carried out at 50 DEG C for 3 h under a nitrogen atmosphere. The reaction product is washed with deionized water for 3 times, and then dried and sieved through a 200-mesh screen to obtain the modified alunite.
[0026] The mass ratio of the activated alunite, KH-560 and the ethanol solution in step (2) is 100:5:300; and the mass ratio of ethanol and water in the ethanol solution is 95:5.
[0027] The amount of potassium persulfate added in step (3) is 0.3% of the mass of the alunite prepared in step (2); and the amount of ascorbic acid added is 0.15% of the mass of the alunite prepared in step (2).
[0028] The water-retaining agent comprises cellulose ether and high-molecular water-absorbing resin, and the mass ratio of the two is 1:1.
[0029] A preparation method of micro-expansion self-compacting concrete comprises the following steps: First, a composite expansion agent is prepared by adding cement, fly ash, mineral powder, natural sand, gravel and other dry materials into a mixer and dry-mixing for 2-3 min until uniform; then the composite expansion agent and polycarboxylate superplasticizer are mixed and slowly added into the dry materials, and stirred for 3-5 min; finally, water and a water-retaining agent are added to form a uniform slurry, thereby obtaining the micro-expansion self-compacting concrete.
[0030] Example 2 A micro-expansion self-compacting concrete comprises the following raw materials by weight: cement 430 parts, fly ash 90 parts, mineral powder 65 parts, natural sand 710 parts, gravel 950 parts, composite expansion agent 12 parts, polycarboxylate superplasticizer 12 parts, water 155 parts, and water-retaining agent 5 parts.
[0031] The composite expansion agent comprises modified plant protein and modified alunite, and the mass ratio of the two is 1:2.
[0032] The preparation method of the modified plant protein is as follows: (1) Protein extraction: Lemna is washed with clean water, dried at 50℃ until the moisture content is less than 10%, and sieved through a 100-mesh sieve. The plant protein is extracted by alkali dissolution and acid precipitation to obtain Lemna protein powder; (2) Enzymatic hydrolysis: 10 g of Lemna protein is dissolved in 100 mL of PBS, 0.1 g of alkaline protease is added, the pH is adjusted to 9.0, and the mixture is hydrolyzed at 37℃ for 4 h. The enzyme is inactivated by heating at 100℃ for 10 min. The hydrolyzed protein is collected by centrifugation; (3) Graft copolymerization: The hydrolyzed protein is dissolved in 100 mL of deionized water, the pH is adjusted to 9.0, 1 g of sodium methallyl sulfonate and 0.1 g of 5% ammonium persulfate are added, and the mixture is reacted at 50℃ for 3 h. The pH is adjusted to 7.0, and the mixture is freeze-dried; (4) Cross-linking modification: Glutamine transaminase is taken, 10 mL of deionized water is added, and the mixture is stirred for 30 min. The grafted protein is dispersed in 100 mL of PBS, and the glutamine transaminase solution is slowly added dropwise. The pH is adjusted to 6.5, the mixture is reacted at 50℃ for 2 h, and then the pH is adjusted to 7.0 to terminate the reaction. The mixture is centrifuged and freeze-dried to obtain the modified plant protein.
[0033] The amount of glutamine transaminase used in step (4) is 3% of the mass of the grafted protein.
[0034] The preparation method of the modified alunite is: (1) soaking alunite in 60℃ 1% sulfuric acid solution for 1h to obtain activated alunite; (2) adding KH-560 into ethanol solution, then adding the activated alunite, reacting for 1h under 70℃ in nitrogen atmosphere, washing with ethanol, and drying; (3) adding 10% glycidyl methacrylate and initiator potassium persulfate and ascorbic acid into the alunite prepared in step (2), reacting for 3h under 50℃ in nitrogen atmosphere, washing the reaction product with deionized water for 3 times, and drying and sieving through 200 mesh to obtain modified alunite.
[0035] The mass ratio of the activated alunite, KH-560 and ethanol solution in step (2) is 100:5:300; the mass ratio of ethanol and water in the ethanol solution is 95:5.
[0036] The adding amount of potassium persulfate in step (3) is 0.3% of the mass of the alunite prepared in step (2); the adding amount of ascorbic acid is 0.15% of the mass of the alunite prepared in step (2).
[0037] The water-retaining agent comprises cellulose ether and high molecular water-absorbing resin, and the mass ratio of the two is 2:1.
[0038] A preparation method of micro-expansion self-compacting concrete comprises the following steps: First, a composite expansion agent is prepared by adding cement, fly ash, mineral powder, natural sand, gravel and other dry materials into a mixer and dry mixing for 2-3min until uniform; then the composite expansion agent and polycarboxylic acid water reducing agent are mixed and slowly added into the dry materials, and stirred for 3-5min; finally, water and water-retaining agent are added to form a uniform slurry, and micro-expansion self-compacting concrete is obtained.
[0039] Example 3 A micro-expansion self-compacting concrete comprises the following raw materials by weight: cement 460 parts, fly ash 120 parts, mineral powder 80 parts, natural sand 850 parts, gravel 1100 parts, composite expansion agent 15 parts, polycarboxylic acid water reducing agent 15 parts, water 160 parts, and water-retaining agent 6 parts.
[0040] The composite expansion agent comprises modified plant protein and modified alunite, and the mass ratio of the two is 1:2.
[0041] The preparation method of the modified plant protein is: (1) protein extraction: washing duckweed with clean water, drying at 50℃ until the moisture content is <10%, sieving through 100 mesh, and extracting plant protein by alkali dissolution and acid precipitation to obtain duckweed protein powder; (2) Enzymatic hydrolysis: 10 g of duckweed protein was dissolved in 100 mL of PBS, 0.1 g of alkaline protease was added, the pH was adjusted to 9.0, and the solution was hydrolyzed at 37°C for 4 h. The enzyme was inactivated by heating at 100°C for 10 min. The hydrolyzed protein was collected by centrifugation. (3) Graft copolymerization: The hydrolyzed protein was dissolved in 100 mL of deionized water, the pH was adjusted to 9.0, 1 g of sodium methacrylsulfonate and 0.1 g of 5% ammonium persulfate were added, and the solution was reacted at 50°C for 3 h. The pH was adjusted to 7.0, and the solution was freeze-dried. (4) Cross-linking modification: The glutamine transpeptidase was dissolved in 10 mL of deionized water and stirred for 30 min. The grafted copolymerized protein was dispersed in 100 mL of PBS, and the glutamine transpeptidase solution was slowly added. The pH was adjusted to 6.5, and the solution was reacted at 50°C for 2 h. The pH was adjusted to 7.0 to terminate the reaction. The solution was centrifuged and freeze-dried to obtain the modified plant protein.
[0042] The amount of glutamine transpeptidase used in step (4) is 3% of the mass of the grafted protein.
[0043] The preparation method of the modified alunite is as follows: (1) Alunite was soaked in 1% sulfuric acid solution at 60°C for 1 h to obtain activated alunite. (2) KH-560 was added to an ethanol solution, and then the activated alunite was added. The solution was reacted at 70°C for 1 h under nitrogen atmosphere, washed with ethanol, and dried. (3) In step (2), 12% of glycidyl methacrylate, initiator potassium persulfate, and ascorbic acid were added to the prepared alunite. The solution was reacted at 50°C for 3 h under nitrogen atmosphere. The reaction product was washed with deionized water three times and dried to pass a 200-mesh sieve to obtain the modified alunite.
[0044] In step (2), the mass ratio of activated alunite, KH-560, and ethanol solution is 100:5:300. In the ethanol solution, the mass ratio of ethanol and water is 95:5.
[0045] In step (3), the amount of potassium persulfate added is 0.3% of the mass of the alunite prepared in step (2), and the amount of ascorbic acid added is 0.15% of the mass of the alunite prepared in step (2).
[0046] The water-retaining agent includes cellulose ether and high-molecular water-absorbing resin, and the mass ratio of the two is 3:1.
[0047] A preparation method of micro-expanding self-compacting concrete includes the following steps: First, the composite expansion agent is prepared, the dry materials such as cement, fly ash, mineral powder, natural sand, gravel, etc. are added into the mixer and dry-mixed for 2-3 min until uniform; then the composite expansion agent and the polycarboxylate superplasticizer are mixed and slowly added into the dry materials, and stirred for 3-5 min; finally, water and water retaining agent are added to form a uniform slurry, and the micro-expanding self-compacting concrete is obtained.
[0048] Comparative Example 1 A micro-expanding self-compacting concrete, comprising the following raw materials by weight: cement 460 parts, fly ash 120 parts, mineral powder 80 parts, natural sand 850 parts, gravel 1100 parts, expansion agent 15 parts, polycarboxylate superplasticizer 15 parts, water 160 parts, water retaining agent 6 parts.
[0049] The expansion agent is modified plant protein.
[0050] The preparation method of the modified plant protein is: (1) Protein extraction: Lemna was washed with clean water, dried at 50℃ until the moisture content was <10%, and sieved through a 100 mesh sieve. The plant protein was extracted by alkali dissolution and acid precipitation to obtain Lemna protein powder; (2) Enzymatic hydrolysis: 10g of Lemna protein was dissolved in 100mL of PBS, 0.1g of alkaline protease was added, the pH was adjusted to 9.0, and hydrolysis was carried out at 37℃ for 4h. The enzyme was inactivated by heating at 100℃ for 10min, and the hydrolyzed protein was collected by centrifugation; (3) Graft copolymerization: the hydrolyzed protein was dissolved in 100ml of deionized water, the pH was adjusted to 9.0, 1g of sodium methacrylsulfonate and 0.1g of 5% ammonium persulfate were added, and the reaction was carried out at 50℃ for 3h. The pH was adjusted to 7.0, and the product was freeze-dried; (4) Cross-linking modification: glutamine transaminase was taken and 10ml of deionized water was added, and stirred for 30min. The grafted protein was dispersed in 100mL of PBS, and the glutamine transaminase solution was slowly added dropwise. The pH was adjusted to 6.5, the reaction was carried out at 50℃ for 2h, and then the pH was adjusted to 7.0 to terminate the reaction. The product was centrifuged and freeze-dried to obtain the modified plant protein.
[0051] The amount of glutamine transaminase used in step (4) is 3% of the mass of the grafted protein.
[0052] The water retaining agent comprises cellulose ether and high molecular water absorbing resin, and the mass ratio of the two is 3:1.
[0053] A preparation method of a micro-expanding self-compacting concrete, comprising the following steps: First, the expansion agent is prepared, and the dry materials such as cement, fly ash, mineral powder, natural sand, gravel, etc. are added into the mixer and dry-mixed for 2-3 min until uniform; then the expansion agent and polycarboxylate superplasticizer are mixed and slowly added into the dry materials, and stirred for 3-5 min; finally, water and water-retaining agent are added to form a uniform slurry, and the micro-expanding self-compacting concrete is obtained.
[0054] The comparative example is compared with example 3, and the rest of the raw materials and steps are the same as example 3, except that the composite expansion agent only uses modified plant protein.
[0055] Comparative example 2 A micro-expanding self-compacting concrete, comprising the following raw materials by weight: cement 460 parts, fly ash 120 parts, mineral powder 80 parts, natural sand 850 parts, gravel 1100 parts, expansion agent 15 parts, polycarboxylate superplasticizer 15 parts, water 160 parts, water-retaining agent 6 parts.
[0056] The expansion agent comprises modified alunite.
[0057] The preparation method of the modified alunite is: (1) soak the alunite in a 1% concentration sulfuric acid solution at 60℃ for 1h to obtain activated alunite; (2) add KH-560 to an ethanol solution, then add the activated alunite, react at 70℃ for 1h under nitrogen atmosphere, then wash with ethanol and dry; (3) add 12% by mass of glycidyl methacrylate and initiator potassium persulfate and ascorbic acid to the alunite prepared in step (2), react at 50℃ for 3h under nitrogen atmosphere, wash the reaction product with deionized water for 3 times, and dry and pass through a 200 mesh sieve to obtain modified alunite.
[0058] The mass ratio of the activated alunite, KH-560 and ethanol solution in step (2) is 100:5:300; the mass ratio of ethanol and water in the ethanol solution is 95:5.
[0059] The addition amount of potassium persulfate in step (3) is 0.3% of the mass of the alunite prepared in step (2); the addition amount of ascorbic acid is 0.15% of the mass of the alunite prepared in step (2).
[0060] The water-retaining agent comprises cellulose ether and high molecular water-absorbing resin, and the mass ratio of the two is 3:1.
[0061] A preparation method of a micro-expanding self-compacting concrete, comprising the following steps: First, the expansion agent is prepared, and the dry materials such as cement, fly ash, mineral powder, natural sand, gravel, etc. are added to the mixer and dry-mixed for 2-3 min until uniform; then the expansion agent and the polycarboxylate superplasticizer are mixed and slowly added to the dry materials, and stirred for 3-5 min; finally, water and water retaining agent are added to form a uniform slurry, and a micro-expanding self-compacting concrete is obtained.
[0062] The team ratio is compared with Example 3, except that the expansion agent is only modified alunite, and the rest of the raw materials and steps are the same as Example 3.
[0063] Comparative Example 3 A micro-expanding self-compacting concrete includes the following raw materials by weight: cement 460 parts, fly ash 120 parts, mineral powder 80 parts, natural sand 850 parts, gravel 1100 parts, composite expansion agent 15 parts, polycarboxylate superplasticizer 15 parts, water 160 parts, and water retaining agent 6 parts.
[0064] The composite expansion agent includes modified plant protein and alunite, and the mass ratio of the two is 1:2.
[0065] The preparation method of the modified plant protein is as follows: (1) Protein extraction: wash duckweed with clean water, dry at 50℃ until the moisture content is <10%, pass through a 100-mesh sieve, and extract plant protein by alkali dissolution and acid precipitation to obtain duckweed protein powder; (2) Enzymatic hydrolysis: dissolve 10g duckweed protein in 100mL PBS, add 0.1g alkaline protease, adjust the pH to 9.0, hydrolyze at 37℃ for 4h, and then heat at 100℃ for 10min to inactivate the enzyme. Collect the hydrolyzed protein by centrifugation; (3) Graft copolymerization: dissolve the hydrolyzed protein in 100ml deionized water, adjust the pH to 9.0, add 1g sodium methacrylsulfonate and 0.1g 5% ammonium persulfate, react at 50℃ for 3h, adjust the pH to 7.0, and freeze-dry; (4) Cross-linking modification: take glutamine transaminase, add 10ml deionized water, and stir for 30min; disperse the graft copolymerized protein in 100mL PBS, slowly add the glutamine transaminase solution, adjust the pH to 6.5, react at 50℃ for 2h, then adjust the pH to 7.0 to terminate the reaction, centrifuge, and freeze-dry to obtain the modified plant protein.
[0066] The amount of glutamine transaminase used in step (4) is 3% of the mass of the grafted protein.
[0067] The water retaining agent includes cellulose ether and high molecular water absorbing resin, and the mass ratio of the two is 3:1.
[0068] A preparation method of a micro-expanding self-compacting concrete includes the following steps: First, the composite expansion agent is prepared, the dry materials such as cement, fly ash, mineral powder, natural sand, gravel, etc. are added into the mixer, and dry mixing is carried out for 2-3 min until uniform; then the composite expansion agent and the polycarboxylate superplasticizer are mixed, and then slowly added into the dry materials, and stirring is carried out for 3-5 min, and finally water and water retaining agent are added to form a uniform slurry, and the micro-expanding self-compacting concrete is obtained.
[0069] The comparative example is compared with example 3, and the raw materials and steps are the same as those of example 3 except that the alunite is not modified.
[0070] Performance test The concrete prepared in examples 1-3 and comparative examples 1-3 is tested, and the specific performance test method is as follows: Compressive strength: refer to standard GB / T 50081-2016 "Standard for testing the mechanical properties of ordinary concrete"; Expansion degree, T500, expansion rate, bleeding rate, gap passing property: refer to JGJ / T 283-2012 "Technical specification for application of self-compacting concrete".
[0071] Table 1: performance test results of concrete in each treatment group
[0072] From the data in table 1, it can be seen that the micro-expanding self-compacting concrete has high compressive strength, anti-segregation property and fluidity, and good expansion rate. Compared with comparative example 1 and comparative example 2, the expansion degree and T500 of example 3 are significantly better than those of comparative example 1 and comparative example 2, which shows that the synergistic effect of modified plant protein and modified alunite in the composite expansion agent has a significant effect on the self-compacting property of the concrete. In addition, the test performance results of the example and the comparative example show that the micro-expanding self-compacting concrete has good anti-segregation property and gap passing property, which shows that the micro-expanding self-compacting concrete has better working performance.
[0073] It should be noted that the above examples are only part of the preferred modes of implementing the present application, but not all. Obviously, based on the above examples of the present application, all other examples obtained by those skilled in the art without creative labor should belong to the scope of protection of the present application.
Claims
1. A micro-expansion self-compacting concrete, characterized in that, The raw materials include the following parts by weight: 400-460 parts cement, 50-120 parts fly ash, 50-80 parts mineral powder, 570-850 parts natural sand, 800-1100 parts crushed stone, 10-15 parts composite expansion agent, 8-15 parts polycarboxylate superplasticizer, 150-160 parts water, and 4-6 parts water-retaining agent.
2. The micro-expansion self-compacting concrete according to claim 1, characterized in that, The composite expanding agent comprises modified plant protein and modified alum stone, with a mass ratio of 1:
2.
3. The micro-expansion self-compacting concrete according to claim 2, characterized in that, The method for preparing the modified plant protein is as follows: (1) Protein extraction: Duckweed is washed with clean water, dried at 50℃ until the moisture content is <10%, passed through a 100-mesh sieve, and plant protein is extracted by alkaline dissolution and acid precipitation to obtain duckweed protein powder; (2) Enzymatic hydrolysis: Dissolve 10g of duckweed protein in 100mL of PBS, add 0.1g of alkaline protease, adjust the pH to 9.0, hydrolyze at 37℃ for 4h, deheat at 100℃ for 10min to inactivate the enzyme, centrifuge and collect the supernatant to collect the hydrolyzed protein; (3) Graft copolymerization: Dissolve the hydrolyzed protein in 100ml of deionized water, adjust the pH to 9.0, add 1g of sodium methyl methacrylate and 0.1g of 5% ammonium persulfate, react at 50℃ for 3h, adjust the pH to 7.0, and freeze dry; (4) Cross-linking modification: Take glutamine transferase, add 10 ml of deionized water, and stir for 30 min; disperse the grafted copolymerized protein in 100 mL of PBS, slowly add glutamine transferase solution, adjust the pH to 6.5, react at 50 °C for 2 h, then adjust the pH to 7.0 to terminate the reaction, centrifuge, and freeze dry to obtain modified plant protein.
4. The micro-expansion self-compacting concrete according to claim 3, characterized in that, In step (4), the amount of glutamine transferase used is 3% of the amount of protein after grafting.
5. The micro-expansion self-compacting concrete according to claim 2, characterized in that, The preparation method of the modified alunite is as follows: (1) Alum stone was soaked in 1% sulfuric acid solution at 60℃ for 1 hour to obtain activated alum stone; (2) Add KH-560 to the ethanol solution, then add the activated alum stone, react at 70°C for 1 h under a nitrogen atmosphere, wash with ethanol and dry. (3) Add 8-12% by mass of glycidyl methacrylate, potassium persulfate and ascorbic acid to the alum stone prepared in step (2), react at 50°C for 3 hours in a nitrogen atmosphere, wash the reaction product with deionized water 3 times, dry and pass through a 200-mesh sieve to obtain modified alum stone.
6. The micro-expansion self-compacting concrete according to claim 5, characterized in that, In step (2), the mass ratio of activated alum stone, KH-560 and ethanol solution is 100:5:300; the mass ratio of ethanol and water in the ethanol solution is 95:
5.
7. The micro-expansion self-compacting concrete according to claim 5, characterized in that, In step (3), the amount of potassium persulfate added is 0.3% of the mass of alum stone obtained in step (2); the amount of ascorbic acid added is 0.15% of the mass of alum stone obtained in step (2).
8. The micro-expansion self-compacting concrete according to claim 1, characterized in that, The water-retaining agent includes cellulose ether and superabsorbent polymer, with a mass ratio of (1-3):
1.
9. A method for preparing micro-expansion self-compacting concrete according to any one of claims 1-8, characterized in that, Preparation includes the following steps: First, prepare the composite expansion agent. Add dry materials such as cement, fly ash, mineral powder, natural sand, and crushed stone to the mixer and dry mix for 2-3 minutes until uniform. Then, mix the composite expansion agent and polycarboxylate superplasticizer and slowly add them to the dry materials. Stir for 3-5 minutes. Finally, add water and water-retaining agent until a uniform paste is formed, thus obtaining micro-expansion self-compacting concrete.